Sustainable groundwater resource extraction influenced by changing climate and pit lake expansion in East Bohemia, Czech Republic - Petr Vaníček; Adam Říčka; Tomáš Kuchovský; Bibiána Pasternáková; Kateřina Chroustová; Karel Šuhajda (Journal of Hydrology: Regional Studies)
Study region: Ceperka groundwater resource, East Bohemia region, Czech Republic Study focus: The expansion of the pit lakes with negative water table balance threatens the Ceperka groundwater resource sustainability. The expected change in the water table balance was estimated according to climate projections. A numerical model was developed to examine how the sustainable extraction could change during the 21st century assuming the pit lakes continue to expand and climate change progresses. New hydrological insights for the region: Evaluation of the water table balance indicates that the current specific water loss of 6 L/s/km2 is expected to increase to 7.2 L/s/km2 in the period 2061–2090 assuming a medium climate scenario. The change in the water table balance of the pit lakes expanding at a rate of 1 km2/20 years would decrease the sustainable extraction by 6 % alone. However, climate change is also responsible for the decline of groundwater recharge and water levels. When this is considered, the sustainable extraction would reduce by 18 % in 2061–2090. Continuing on this trajectory would result in a water supply shortage within approximately forty years from now. It appears that the change in hydrogeological conditions has a significant impact as well. Still, an additional pit lake expansion should be carefully considered in areas with a negative water table balance to mitigate the decrease in sustainable extraction.